Evaluasi Perbandingan Kinerja Bangunan Momen Frame dengan Eccentrycally Brace Frame - Sumargo; Rheza Andhy K; Hermansa (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2008)
Generally, earthquake resistant design is based on elastic structural analysis with load factor to simulate ultimate condition. Actually, behavior of collapse structures during earthquake is in-elastic. Evaluation to predict in-elastic condition of structures during earthquake is needed in order to guarantee that it can perform well during earthquake. Analysis and performance evaluation can be done with pushover analysis given in SAP2000, while evaluation of performance point must be determined manually with various methods (except for capacity spectrum method). Pushover analysis is a non linear static analysis as a behavior of structural failure due to earthquake, while performance point is structural maximum displacement during design earthquake. Study on steel frame 3D concludes that performance evaluation for pushover in longitudinal direction according to ATC-40 gives displacement target for moment frame building of 0.054 m, building with eccentrically braced frame (EBF): 0.022 m. Pushover in transverse direction according to ATC-40 gives displacement target for moment frame building of 0.022 m, building with EBF: 0.015 m. According to FEMA 356, displacement target in longitudinal direction for moment frame building: 0.0803 m, building with (EBF): 0.0728 m. For building with moment frame in transverse direction: 0.1183 m, building with (EBF): 0.0614 m.